Genetic analysis for panicle characters in diallel cross of rice (Bangladesh Journal of Agricultural Research, 2009)
An experiment was carried out to study the genetic components for eight panicle characters in rice using an 8-parent half diallel cross excluding reciprocals during Transplant Aman season, 2003. The parental genotypes used in the study were BRRI dhan29, BR4828-54-4-l-4-9, BRR1 dhan28, 1R8, Amol3, 1R65610-38-2-4-2-6-3, Minikit and ZhongYu7, which were chosen for their diversity in panicle characters. Hayman's analysis of variance (ANOVA) indicated importance of both additive and non-additive genetic components for all the panicle characters except dominance component for filled grains/secondary branches. The ANOVA showed unidirectional dominance for the characters viz, primary branch length, secondary branch length, primary branches/panicle, secondary branches/panicle and filled grains/primary branch, asymmetrical gene distribution for all the panicle traits except filled grains/secondary branch and residual dominance effects for all the panicle characters studied. Two out of eight panicle characters viz., primary branches/panicle and unfilled grains/ secondary branch followed the simple additive-dominance genetic model. The rest of the panicle characters showed nonallelic gene interaction or epistasis. According to Vr-Wr graph, partial dominance was involved in the action of genes governing the inheritance of primary branches/panicle, while complete dominance was involved in the inheritance of unfilled grains/secondary branch. Most of the dominant genes for primary branches/panicle belonged to other hand, 1R8 possessed most of the dominant genes, while 1R65610-38-2-4-2-6-3 possessed most of the recessive genes for unfilled grains/secondary branch. The estimates of components of variance demonstrated involvement of both additive and dominant components in the inheritance of primary branches/panicle and unfilled grains/secondary branch. The distribution of dominant and recessive genes was unequal in the parents for these two characters also. There was drastic influence of environment on these two panicle characters following simple additive-dominance genetic model. Heritability in narrow sense (h2 ns) was very high for primary branches/panicle and unfilled grains/secondary branch. Key Words: Genetic analysis, diallel cross, panicle characters, rice. doi: 10.3329/bjar.v33i4.2307 Bangladesh J. Agril. Res. 33(4) : 631-638, December 2008